Chinese Herbal Medicine as a Potential Treatment of Abdominal Aortic Aneurysm - Seto, Sai Wang; Chang, Dennis; Kiat, Hosen; Wang, Ning; Bensoussan, Alan (Frontiers in Cardiovascular Medicine, 2018)
Abdominal aortic aneurysm (AAA) is an irreversible condition where the abdominal aorta is dilated leading to potentially fatal consequence of aortic rupture. Multiple mechanisms are involved in the development and progression of AAA, including chronic inflammation, oxidative stress, vascular smooth muscle (VSMC) apoptosis, immune cell infiltration and extracellular matrix (ECM) degradation. Currently surgical therapies, including minimally invasive endovascular aneurysm repair (EVAR), are the only viable interventions for AAAs. However, these treatments are not appropriate for the majority of AAAs, which measure < 50mm. Substantial effort has been invested to identify and develop pharmaceutical treatments such as statins and doxycycline for this potentially lethal condition but these interventions failed to offer a cure or to retard the progression of AAA. Chinese herbal medicine (CHM) has been used for the management of cardiovascular diseases for thousands of years in China and other Asian countries. The unique multi-component and multi-target property of CHMs makes it a potentially ideal therapy for multifactorial diseases such as AAA. In this review, we review the current scientific evidence to support the use of CHMs for the treatment of AAA. Mechanisms of action underlying the effects of CHMs on AAA are also discussed.